Innate immunity and metabolomic responses in dairy cows challenged intramammarily with lipopolysaccharide after subacute ruminal acidosis. (13th March 2018) - Humer, E.; Aditya, S.; Zebeli, Q.
Abstract : Subacute ruminal acidosis (SARA) is a prevalent metabolic disorder in dairy cows known to elicit local and systemic immune responses. We recently showed that cows experiencing SARA and challenged intramammarily with lipopolysaccharide (LPS) experienced stronger metabolic disturbances compared with cows without SARA. Therefore, we hypothesized that cows experiencing SARA have a modulated innate immune response and impaired plasma metabolome compared with healthy cows when experiencing an acute mastitis challenge. A total of 18 Simmental cows were subjected either to a Control (CON, n =6) or SARA ( n= 12) feeding regimen, receiving either 40% or 60% concentrates for 30 days. Thereafter, six SARA (SARA-LPS) and the CON (CON-LPS) cows were intramammarily challenged with 50 µg LPS from Escherichia coli (O26 : B6), while the remaining six SARA cows (SARA-PLA) received a placebo. Blood and milk samples were analyzed for acute phase proteins and a targeted ESI-LC-MS/MS-based metabolomics approach was performed in blood samples 24 h after the LPS challenge. The LPS infusion caused a strong increase in immune response variables, with a higher concentration of milk amyloid A 48 h after the LPS challenge in SARA-LPS compared with CON-LPS cows. Cows receiving the LPS infusion had a lower plasma concentration of several amino acids and lysophosphatidylcholines but without differences in SARA cows and healthy cows. In conclusion, our results revealed that an intramammary LPS infusion increased acute phase proteins and modulated the blood metabolome. While no systemic differences between SARA and healthy cows were observed, cows experiencing SARA showed a higher concentration of an acute phase protein at the local level of the mammary gland. Further research is required to elucidate the underlying mechanisms and to evaluate its clinical significance for udder health.